Complications after Endovascular Aneurysm Repair - Geert Maleux; Marcel Koolen; Sam Heye (2009)
Endovascular aneurysm repair (EVAR) has become an established technique for the treatment of many infrarenal aortic aneurysms. Although EVAR is obviously less invasive than open surgical repair, it is not free of complications. These can potentially result in severe morbidity or even mortality, stressing the need for an early detection and subsequent treatment. In this review article, the pathophysiology, diagnosis, and treatment of the most common complications of EVAR, with the exception of endoleaks, are described.